O Papel da Comunicação e da Mobilização em Projetos Públicos: Análise do Projeto Cidade Eficiente (Elói Mendes-MG) - Kenya Adryene Valadares Moreira Cruz (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2013)
This article presents a survey about the population's perception in city of Eloi Mendes - Minas Gerais, to the role of communication and mobilization for change of habit in the use of electricity. Were analyzed an energy efficiency project: Efficient City, deploys in the city between the years 2001 and 2003. The research was performed by questionnaires deploys in the Eloi Mendes' homes. The results indicate the communication and mobilization, as design elements, support for change of consumption' habit.